Magnetic composite adsorbent for removing malachite green dye as well as preparation method and application of magnetic composite adsorbent
The magnetic composite adsorbent prepared by the sol-gel one-pot method has the main components of mafite, α-ferric oxide and carbon materials, which solves the problems of low efficiency and high cost of removing high-concentration malachite green dyes in the prior art, and achieves an efficient and environmentally friendly dye removal effect, and the adsorbent can be recycled and utilized multiple times.
Patent Information
- Application Number
- CN202510140778.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art has problems such as low treatment efficiency, high cost and difficulty in separating adsorbents when removing high-concentration malachite green dyes in industrial wastewater.
By using choline chloride and oxalic acid as mixed solvents, magnetic composite adsorbents were prepared by the sol-gel one-pot method, and the main components included mafite, α-ferric oxide and carbon materials.
It has achieved efficient removal of malachite green dye, with high removal rate, short removal time, simple preparation method and low cost, and can be recycled and reused, environmentally friendly and energy-saving.
Smart Images

Figure CN119771377A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorbents, and in particular to a magnetic composite adsorbent for removing malachite green dye, and a preparation method and application thereof. Background Art
[0002] Malachite green is a triphenylmethane cationic dye widely used in printing and dyeing, papermaking, food, cosmetics and other industries. Malachite green is difficult to remove in the environment and may have negative impacts on ecosystems and human health. Therefore, it is urgent and challenging to efficiently remove malachite green from industrial wastewater.
[0003] Among the many methods for treating dye wastewater, photocatalysis and adsorption are both very common and effective treatment methods. Among them, although the photocatalysis method has the advantages of high treatment efficiency and the ability to destroy the molecular structure of dyes, its treatment effect is often affected by factors such as light conditions, catalyst types and stability. In addition, the photocatalysis method may face problems such as catalyst deactivation and decreased treatment efficiency when treating high-concentration dye wastewater, and the photocatalysis method can only treat dye wastewater with lower concentrations. The adsorption method is suitable for treating wastewater of various concentrations and types, has strong adaptability, and can be carried out without light conditions. Different types of adsorbents can adsorb different types of dye molecules, thereby achieving extensive treatment of wastewater. The adsorption method does not require the addition of chemical reagents, does not produce secondary pollution, and is harmless to the environment. In addition, the price of the adsorbent is relatively low and can be recycled, thereby reducing the treatment cost. In addition, the treatment process of the adsorption method is simple, does not require complex equipment and operations, and further reduces the economic cost.
[0004] Therefore, adsorption has become one of the most promising and effective treatment methods due to its low cost, simple operation, high applicability, environmental friendliness, reusability, high treatment efficiency and non-toxic byproducts. In addition, since magnetism makes it easy to separate materials in adsorption materials, the application prospects of magnetic composite materials are even broader. The adsorption method uses adsorbents to adsorb dyes from water to solid surfaces. Common adsorbents include activated carbon, silica gel, biochar, etc.
[0005] As a widely used adsorbent material, biochar comes from nature, has good biocompatibility and renewability, and has a strong ability to remove pollutants from wastewater. However, biochar also has limitations in its adsorption capacity in removing pollutants from wastewater, especially when treating high-concentration wastewater. Therefore, in order to enhance the removal effect of biochar on spinel-type magnesium ferrite pollutants, many studies have begun to try to modify biochar materials. For example, using spinel cobalt ferrite as a modified material, biochar-based adsorbent materials were designed and synthesized through hydrothermal, coprecipitation and pyrolysis methods. However, the synthesis process of this approach is extremely complicated and the cost of raw materials is high.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first purpose of the present invention is to provide a method for preparing a magnetic composite adsorbent for removing malachite green dye. Choline chloride and oxalic acid are used as a mixed solvent and the magnetic composite adsorbent is prepared by a sol-gel one-pot process. The synthesis method is simple, the process is short, the raw material source is wide, the price is low, and the prepared magnetic composite adsorbent has a good treatment effect on malachite green dye, a high removal rate, and a short removal time.
[0008] The second purpose of the present invention is to provide a magnetic composite adsorbent for removing malachite green dye, which has low production cost, high removal rate and short removal time for malachite green, can be recycled and reused after use, and the magnetic composite adsorbent still has a high removal rate for malachite green after multiple recycling, is environmentally friendly and energy-saving, and has high added value.
[0009] The third object of the present invention is to provide an application of a magnetic composite adsorbent for removing malachite green dye.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] The present invention firstly provides a preparation method of a magnetic composite adsorbent for removing malachite green dye, comprising the following steps: mixing choline chloride, oxalic acid, a magnesium source, an iron source and citric acid and carrying out a complex reaction to obtain a sol; adjusting the pH of the sol and heating to obtain a gel; igniting the gel and obtaining a precursor after combustion; and calcining the precursor to obtain the magnetic composite adsorbent for removing malachite green dye.
[0012] Furthermore, the molar ratio of the magnesium element in the magnesium source to the iron element in the iron source is 1.2-1.6:2.
[0013] Furthermore, the molar ratio of the choline chloride to the oxalic acid is 0.5-1.5:1.5-2.5;
[0014] Furthermore, the ratio of the molar amount of the citric acid to the sum of the molar amounts of the magnesium element in the magnesium source and the iron element in the iron source is 1 to 1.5:1.
[0015] Furthermore, the temperature of the complexation reaction is 40-90°C.
[0016] Further, the pH of the sol is adjusted to 7-11;
[0017] Furthermore, the calcination temperature is 450-900°C.
[0018] The present invention further provides a magnetic composite adsorbent for removing malachite green dye, which is mainly prepared by the preparation method of the magnetic composite adsorbent for removing malachite green dye.
[0019] Furthermore, main components of the magnetic composite adsorbent for removing malachite green dye include magnesium ferrite, α-ferric oxide and carbon material.
[0020] The present invention also provides application of the magnetic composite adsorbent for removing malachite green dye in removing malachite green dye.
[0021] Furthermore, the magnetic composite adsorbent for removing malachite green dye has a removal rate of ≥90% for malachite green solution with a concentration of ≤100 mg / L.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention provides a method for preparing a magnetic composite adsorbent for removing malachite green dye. Choline chloride and oxalic acid are used as a mixed solvent and the magnetic composite adsorbent is prepared by a sol-gel one-pot process. The synthesis method is simple, easy to operate, and suitable for large-scale production. The raw material cost is low and the raw material source is wide. The magnetic composite adsorbent prepared by the method has a good removal effect on malachite green dye, a high removal rate, and a short removal time.
[0024] (2) The present invention provides a method for preparing a magnetic composite adsorbent for removing malachite green dye. The prepared magnetic composite adsorbent has magnetism and can be recovered and reused multiple times by applying an external magnetic field. After multiple recycling, the magnetic composite adsorbent still has a high removal rate for malachite green, is environmentally friendly and energy-saving, and has high product added value.
[0025] (3) The magnetic composite adsorbent is prepared by a one-pot sol-gel method. In this synthesis process, the spinel will not generate large particles and will not agglomerate. The size is small, thereby ensuring its surface activity. At the same time, it ensures that the composite adsorbent is magnetic and the magnetism is not so strong that it agglomerates during use.
[0026] (4) The magnetic composite adsorbent is prepared by the sol-gel one-pot method. The three components contained in the composite adsorbent are very small in size, and there is good binding force between the components. The binding is stable, and there are many active sites on the surfaces of the three components. The overall specific surface area of the composite adsorbent is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 The XRD diagram of the magnetic composite adsorbent prepared in Example 1 provided by the present invention;
[0029] Figure 2 This is an XPS graph of the magnetic composite adsorbent prepared in Example 1 provided by the present invention;
[0030] Figure 3 A curve showing the change in removal rate of a malachite green solution with a concentration of 50 mg / L by the magnetic composite adsorbent prepared in Example 1 provided by the present invention as a function of treatment time;
[0031] Figure 4 A curve showing the change in removal rate of a malachite green solution with a concentration of 75 mg / L by the magnetic composite adsorbent prepared in Example 1 provided by the present invention as a function of treatment time;
[0032] Figure 5 A curve diagram showing the change in removal rate of a malachite green solution with a concentration of 100 mg / L by the magnetic composite adsorbent prepared in Example 1 provided by the present invention as a function of treatment time;
[0033] Figure 6 A curve diagram showing the change in removal rate of a malachite green solution with a concentration of 50 mg / L by the magnetic composite adsorbent prepared in Example 2 provided by the present invention as a function of treatment time;
[0034] Figure 7 A curve showing the change in removal rate of a malachite green solution with a concentration of 75 mg / L by the magnetic composite adsorbent prepared in Example 2 provided by the present invention as a function of treatment time;
[0035] Figure 8 A curve diagram showing the change in removal rate of a malachite green solution with a concentration of 100 mg / L by the magnetic composite adsorbent prepared in Example 2 provided by the present invention as a function of treatment time;
[0036] Fig. 9 A comparison chart of the removal rates of a malachite green solution with a concentration of 75 mg / L after four cycles of use of the magnetic composite adsorbent provided in Example 1 of the present invention;
[0037] Fig.10This is a comparison chart of the removal rates of a malachite green solution with a concentration of 75 mg / L after four cycles of use of the magnetic composite adsorbent provided in Example 2 of the present invention. DETAILED DESCRIPTION
[0038] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0039] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0040] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0041] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0042] In a first aspect, the present invention provides a method for preparing a magnetic composite adsorbent for removing malachite green dye, comprising the following steps:
[0043] Choline chloride, oxalic acid, a magnesium source, an iron source and citric acid are mixed and subjected to a complex reaction, and a sol is obtained after the reaction is completed.
[0044] The pH of the sol is adjusted and heated to obtain a gel.
[0045] The gel is ignited, and a precursor is obtained after the combustion is completed.
[0046] The precursor is calcined and cooled to obtain the magnetic composite adsorbent for removing malachite green dye.
[0047] The invention provides a method for preparing a magnetic composite adsorbent for removing malachite green dye. Choline chloride and oxalic acid are added during the preparation process. The two can change the ionic strength, solubility, etc. of the reaction system and may also participate in the reaction, thereby changing the mechanism and pathway of the reaction. The addition of the two may also affect the reaction rate and kinetics and change the conditions of the oxidation reaction. These factors affect the composition of the product and cause side reactions to occur. Therefore, the magnetic composite adsorbent contains alpha ferric oxide and carbon material in addition to magnesium ferrite.
[0048] The invention provides a method for preparing a magnetic composite adsorbent for removing malachite green dye. Choline chloride and oxalic acid are used as a mixed solvent, and the magnetic composite adsorbent is prepared by a sol-gel one-pot process. On the one hand, the one-pot synthesis method is simple, magnesium is cheap, and the source of raw materials is wide. On the other hand, the prepared magnetic composite adsorbent has magnetism. After being composited with other materials, not only can the adsorption capacity be increased, but the adsorbent can also be quickly recovered from wastewater by magnetic force, thereby solving the problem that the adsorbent is difficult to separate.
[0049] At the same time, the main components of the magnetic composite adsorbent include magnesium ferrite, and spinel magnesium ferrite has a unique crystal structure and physical and chemical properties, such as high specific surface area, surface active sites and excellent magnetism. These properties make it an efficient and stable adsorbent. When treating malachite green dye wastewater, the magnetic composite adsorbent can quickly adsorb the dye molecules in the wastewater and fix them on the surface of the adsorbent, thereby achieving efficient wastewater purification.
[0050] The method can be used to prepare a magnetic composite adsorbent whose main components are magnesium ferrite, α-ferric oxide and carbon material. The magnetic composite adsorbent has a good treatment effect on malachite green dye, a high removal rate and a short removal time.
[0051] The magnetic composite adsorbent prepared by this method has good stability and repeatability, so it can be used as an adsorbent for treating wastewater and has broad application prospects.
[0052] Specifically, in the present invention, the role of the mixed solvent of choline chloride and oxalic acid includes: (1) in the synthesis process of the magnetic composite adsorbent, it can be both a solvent and a reactant, or used as a template. (2) Since oxalic acid has a low dissociation constant and a small molecular structure, oxalic acid can easily form hydrogen bonds with choline chloride. Therefore, there is a rich hydrogen bond network inside the choline chloride-oxalic acid mixed solvent, which slows down the migration speed of metal ions therein, and the metal complex exists in the spatial network of the gel in a more stable form, thereby avoiding the formation of metal oxide or hydroxide precipitation and improving the dispersion uniformity and stability of the metal in the gel network. (3) The choline chloride-oxalic acid mixed solvent has a low freezing point. Under low temperature conditions, when a certain amount of hydrogen bond acceptors and hydrogen bond donors are mixed, good mixing can be achieved because the freezing point of the mixed solvent is much lower than the freezing points of the pure substances of its components. (4) Using a choline chloride-oxalic acid mixed solvent to prepare the composite adsorbent by a one-pot method can enhance the interaction between the components of magnesium ferrite, α-ferric oxide and carbon material, thereby improving the activity and stability of the composite adsorbent.
[0053] In the sol-gel self-propagating method, the role of citric acid includes: (1) Citric acid can make metal ions evenly dispersed in the citric acid aqueous solution. When the system begins to form a sol state, the steric hindrance of citric acid can reduce the cohesive force between the colloid particles, increase the stability of the colloid particles, and reduce the agglomeration strength, so that the sintered product has a small particle size and is evenly distributed. (2) In the sol-gel self-propagating process, citric acid can also participate in the combustion reaction as a fuel, which helps the reaction and the formation of products. (3) Citric acid can form complexes with metal ions. This complex plays a role in stabilizing metal ions during the formation and combustion of gel, preventing metal ions from segregating or precipitating during the reaction. (4) Citric acid can also be used to adjust the pH value of the sol, thereby controlling the gelation process of the sol and the properties of the product. (5) The addition of citric acid can also affect the microstructure of the material, such as porosity, specific surface area, etc. These factors have a direct impact on the adsorption properties of the material.
[0054] The present invention can control the formation and stability of sol in the sol-gel self-propagating method, the morphology and structure of the gel, and the stability of the metal ions by adjusting the pH of the sol, thereby controlling the microstructure and performance of the material.
[0055] In some specific implementations, during the process of igniting the gel, a small amount of ethanol is added to the gel to ignite it so that it burns more completely.
[0056] The invention can ignite the gel at room temperature, has simple operation and lower energy consumption.
[0057] In order to further improve the removal effect of the prepared magnetic composite adsorbent on malachite green and improve the removal rate, the present invention optimizes the following parameters such as the ratio of choline chloride and oxalic acid, the ratio of metal elements, the amount of citric acid, the pH of the sol, and the temperature and time in the preparation process.
[0058] In some specific embodiments, the molar ratio of the magnesium element in the magnesium source to the iron element in the iron source is 1.2 to 1.6:2, including but not limited to any point value of 1.2:2, 1.3:2, 1.4:2, 1.5:2, 1.6:2 or a range value between any two of them.
[0059] In some specific embodiments, the molar ratio of the choline chloride to the oxalic acid is 0.5-1.5:1.5-2.5, including but not limited to any point value of 0.5:1.5, 1:1.5, 1.5:1.5, 0.5:2, 1:2, 1.5:2, 0.5:2.5, 1:2.5, 1.5:2.5 or a range value between any two of them.
[0060] In some specific embodiments, the ratio of the total volume of the choline chloride and the oxalic acid to the molar amount of the iron element in the iron source is 20 mL to 40 mL: 1.5 mol to 2.5 mol; for example, 20 mL: 1.5 mol, 30 mL: 2 mol or 40 mL: 2.5 mol.
[0061] In some specific embodiments, the ratio of the molar amount of citric acid to the sum of the molar amounts of the magnesium element in the magnesium source and the iron element in the iron source is 1 to 1.5:1, including but not limited to any point value of 1:1, 1.2:1, 1.4:1, 1.5:1 or a range value between any two of them.
[0062] In some specific embodiments, the reaction temperature of the complexation reaction is 40-90°C, including but not limited to any point value of 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or a range between any two of them.
[0063] In some specific embodiments, the reaction time of the complex reaction is ≥10 min, including but not limited to any one of 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 120 min, 180 min, 240 min, 300 min or a range between any two of them.
[0064] In some specific embodiments, the pH of the sol is adjusted to 7-11, including but not limited to any one of 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11 or a range between any two of them.
[0065] In some specific embodiments, the calcination temperature is 450-900°C, including but not limited to any point value of 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C or a range between any two of them.
[0066] In some specific embodiments, the calcination holding time is ≥1h, including but not limited to any one of 1h, 2h, 3h, 4h, 6h, 8h, 10h, 12h, 15h, 20h or a range between any two of them.
[0067] In some specific embodiments, the preparation method of the magnetic composite adsorbent for removing malachite green dye specifically includes: after uniformly mixing choline chloride and oxalic acid, adding a magnesium source and an iron source thereto, stirring for a period of time and then adding citric acid thereto to carry out a complex reaction to obtain a sol.
[0068] In some specific embodiments, the magnesium source includes a magnesium-containing compound, such as magnesium nitrate, but is not limited thereto.
[0069] In some specific embodiments, the iron source includes an iron-containing compound, such as ferric nitrate, but is not limited thereto.
[0070] In a second aspect, the present invention provides a magnetic composite adsorbent for removing malachite green dye, which is mainly prepared by the preparation method of the magnetic composite adsorbent for removing malachite green dye.
[0071] The magnetic composite adsorbent for removing malachite green dye provided by the present invention has low production cost, good treatment effect on malachite green, high removal rate, short removal time, and can be recycled and reused after use, which is environmentally friendly, energy-saving and has high added value.
[0072] In some specific embodiments, the main components of the magnetic composite adsorbent for removing malachite green dye include magnesium ferrite (spinel-type magnesium ferrite), α-ferric oxide and carbon material.
[0073] Wherein, the carbon material includes elemental carbon and organic compounds with functional groups.
[0074] In a third aspect, the present invention provides the use of the magnetic composite adsorbent for removing malachite green dye in the adsorption and removal of malachite green dye.
[0075] The magnetic composite adsorbent for removing malachite green dye provided by the invention has high product added value and can be widely used in the treatment of colored dye wastewater, especially in the removal of malachite green dye.
[0076] In some specific embodiments, the magnetic composite adsorbent for removing malachite green dye has a removal rate of ≥90% for malachite green solution with a concentration of ≤100 mg / L, wherein the removal rate includes but is not limited to any point value of 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5%, 99.8%, 100% or a range value between any two of them.
[0077] In some specific embodiments, the magnetic composite adsorbent for removing malachite green dye has a removal rate of ≥90% for a malachite green solution with a concentration of 50 to 100 mg / L.
[0078] In some specific embodiments, the removal rate of the magnetic composite adsorbent for removing malachite green dye for a malachite green solution with a concentration of 100 mg / L is ≥90%.
[0079] In some specific embodiments, the removal rate of the magnetic composite adsorbent for removing malachite green dye for a malachite green solution with a concentration of 75 mg / L is ≥90%.
[0080] In some specific embodiments, the removal rate of the magnetic composite adsorbent for removing malachite green dye for a malachite green solution with a concentration of 50 mg / L is ≥95%.
[0081] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0082] Example 1
[0083] The preparation method of the magnetic composite adsorbent for removing malachite green dye provided in this embodiment comprises the following steps:
[0084] Choline chloride and oxalic acid in a molar ratio of 1:2 were mixed and magnetically stirred to obtain a choline chloride oxalic acid mixed solvent. 2 mol of ferric nitrate and 1.3 mol of magnesium nitrate were added to the choline chloride oxalic acid mixed solvent with a total volume of 30 mL and stirred evenly, and then 3.4 mol of citric acid was added thereto, and a complexation reaction was carried out at 45° C. to obtain a sol.
[0085] After the pH of the sol is adjusted to 8 with an ammonia solution, the obtained sol is continuously heated to form a gel, and then ethanol is added to the gel and ignited, and a precursor is obtained after the combustion ends.
[0086] The precursor was calcined at 700°C for 2h and cooled to obtain a magnetic composite adsorbent.
[0087] like Figure 1 The XRD pattern of the magnetic composite adsorbent prepared in this embodiment is shown in FIG. Figure 1 It can be seen that the main components of the magnetic composite adsorbent prepared in this embodiment include magnesium ferrite and α-ferric oxide.
[0088] like Figure 2 The XPS graph of the magnetic composite adsorbent prepared in this example is shown in FIG. Figure 2 It can be seen that the main components of the magnetic composite adsorbent prepared in this embodiment include not only magnesium ferrite and α-ferric oxide, but also carbon material.
[0089] Example 2
[0090] The preparation method of the magnetic composite adsorbent for removing malachite green dye provided in this embodiment is basically the same as that in Example 1, except that the molar amount of magnesium nitrate is replaced by 1.5 mol (that is, the molar ratio of the magnesium element in the magnesium source to the iron element in the iron source is 1.5:2), and the molar amount of citric acid is replaced by 5.25 mol (that is, the ratio of the molar amount of citric acid to the sum of the molar amounts of the magnesium element in the magnesium source and the iron element in the iron source is 1.5:1).
[0091] Example 3
[0092] The preparation method of the magnetic composite adsorbent for removing malachite green dye provided in this embodiment is basically the same as that in Example 1, except that the precursor is calcined at 550° C. for 3.5 h.
[0093] Example 4
[0094] The preparation method of the magnetic composite adsorbent for removing malachite green dye provided in this embodiment is basically the same as that in Example 1, except that the reaction temperature of the complex reaction is replaced with 65°C.
[0095] Example 5
[0096] The preparation method of the magnetic composite adsorbent for removing malachite green dye provided in this embodiment is basically the same as that in Embodiment 1, except that the pH of the sol is adjusted to 9 by using an ammonia solution.
[0097] Example 6
[0098] The preparation method of the magnetic composite adsorbent for removing malachite green dye provided in this embodiment is basically the same as that in Example 1, except that the molar ratio of choline chloride to oxalic acid is replaced with 1:1.5.
[0099] Comparative Example 1
[0100] The preparation method of the adsorbent provided in this comparative example is basically the same as that of Example 1, except that the choline chloride and oxalic acid mixed solvent is replaced with an equal volume of deionized water, that is, the synthetic raw materials do not contain choline chloride and oxalic acid.
[0101] Comparative Example 2
[0102] The adsorbent provided in this comparative example is MgFe2O4.
[0103] Comparative Example 3
[0104] The adsorbent provided in this comparative example is α-ferric oxide.
[0105] Comparative Example 4
[0106] The preparation method of the adsorbent provided in this comparative example is basically the same as that of Example 1, except that oxalic acid is replaced with an equal volume of ethylene glycol (ie, no oxalic acid is added) to prepare a choline chloride ethylene glycol mixed solvent.
[0107] Comparative Example 5
[0108] The preparation method of the adsorbent provided in this comparative example is basically the same as that of Example 1, except that oxalic acid is replaced with an equal volume of urea (ie, no oxalic acid is added) to prepare a choline chloride-urea mixed solvent.
[0109] Comparative Example 6
[0110] The preparation method of the adsorbent provided in this comparative example is basically the same as that of Example 1, except that oxalic acid is replaced with an equal volume of glycerol (ie, no oxalic acid is added) to prepare a choline chloride-glycerol mixed solvent.
[0111] Comparative Example 7
[0112] The preparation method of the adsorbent provided in this comparative example is basically the same as that of Example 1, except that choline chloride is replaced with an equal volume of choline bromide (ie, no choline chloride is added) to prepare a choline bromide oxalate mixed solvent.
[0113] Experimental example
[0114] The magnetic composite adsorbents prepared in the above embodiments and the adsorbents prepared in the comparative examples were respectively used to carry out malachite green adsorption tests. After the malachite green adsorption tests were completed, the adsorbents were recovered, and the removal rates and removal times of malachite green by each group of adsorbents were statistically calculated. The results are shown in Table 1.
[0115] Among them, the test method of malachite green adsorption test is as follows: transfer 100 ml of malachite green solution of a certain concentration, measure the initial concentration of the malachite green solution, then add the weighed adsorbent (all 50 mg) into the malachite green solution, stir under natural light, and start timing; take malachite green solution (5 ml) every 20 to 30 minutes, measure the concentration of the supernatant after centrifugation and magnetic separation, and examine its change pattern with time; when the removal equilibrium is reached, calculate the removal rate of the malachite green solution by each adsorbent, separate the magnetic composite adsorbent with a magnet, and then wash and regenerate the magnetic composite adsorbent alternately with anhydrous ethanol and distilled water.
[0116] Table 1 Removal rate of malachite green solution by various adsorbents
[0117]
[0118]
[0119] The removal rate of the magnetic composite adsorbent prepared in Example 1 for 50 mg / L malachite green solution varies with the treatment time. Figure 3 The removal rate of the magnetic composite adsorbent prepared in Example 1 for 75 mg / L malachite green solution changes with the treatment time as shown in Figure 4 The removal rate of the magnetic composite adsorbent prepared in Example 1 for 100 mg / L malachite green solution varies with the treatment time. Figure 5 The removal rate of the magnetic composite adsorbent prepared in Example 2 for 50 mg / L malachite green solution changes with the treatment time as shown in Figure 6 The removal rate of the magnetic composite adsorbent prepared in Example 2 for 75 mg / L malachite green solution changes with the treatment time as shown in Figure 7 The removal rate of the magnetic composite adsorbent prepared in Example 2 for 100 mg / L malachite green solution varies with the treatment time. Figure 8 shown.
[0120] It can be seen from Table 1 that the magnetic composite adsorbents prepared in the embodiments of the present invention have a high removal rate for malachite green of various concentrations, while the adsorbents prepared in the comparative examples have a low removal rate for the dye solution.
[0121] Among them, Comparative Examples 2 and 3 respectively use MgFe2O4 and α-ferric oxide, but the removal rate of the dye solution is significantly lower than that of Example 1, and the removal time is longer, which shows that the components in the magnetic composite adsorbent prepared by the present invention have a synergistic effect.
[0122] However, since unsuitable solvents were used in Comparative Examples 1 and 4 to 7, the removal rates of the obtained adsorbents for the malachite green dye solution were lower than that in Example 1, and the removal time was longer. This shows that the preparation method of the magnetic composite adsorbent for removing malachite green dye provided by the present invention affects the composition of the product by adopting a specific type of solvent, and can improve the removal rate of malachite green dye and shorten the removal time.
[0123] Furthermore, the magnetic composite adsorbent prepared in each embodiment of the present invention can be recycled and reused. The magnetic composite adsorbent recovered in Example 1 and Example 2 was used to continue the adsorption test of malachite green, and the recovery was repeated four times. The comparison chart of the removal rate of 75 mg / L malachite green by the magnetic composite adsorbent provided in Example 1 after four times of repeated recovery is shown in FIG. Fig. 9 As shown, the magnetic composite adsorbent provided in Example 2 was recycled four times for a comparison of the removal rate of 75 mg / L malachite green. Fig.10 As shown. Fig. 9 and Fig.10 It can be seen that after the fourth recovery, the magnetic composite adsorbent still has a high removal rate for 75 mg / L malachite green.
[0124] In summary, the magnetic composite adsorbent prepared by the method provided by the present invention has an obvious removal effect on malachite green dye. The initial concentration of 75mg / L malachite green dye solution is high, the removal rate is high, and the magnetic separation recovery effect of the magnetic composite adsorbent is very good. Within 2h, the removal rate of the first adsorption experiment of Example 1 is 98%, the first removal rate of recycling is 97.03%, the second removal rate of recycling is 94.36%, the third removal rate of recycling is 92.1%, and the fourth removal rate of recycling is 90.41%; within 3h, the removal rate of the first adsorption experiment of Example 2 is 96%, the first removal rate of recycling is 94.17%, the second removal rate of recycling is 91.57%, the third removal rate of recycling is 87.32%, and the fourth removal rate of recycling is 82.89%. When reused, the removal rate remains basically unchanged.
[0125] Therefore, the preparation method of the magnetic composite adsorbent provided by the present invention is simple to operate and low in cost. The magnetic composite adsorbent prepared by the present invention has a high removal rate for malachite green dye and a short removal time, and can be recovered and reused many times. After multiple recycling, the magnetic composite adsorbent still has a high removal rate for malachite green, is environmentally friendly and energy-saving, has a high product added value, and can be widely used in dye removal treatment.
[0126] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a magnetic composite adsorbent for removing malachite green dye, characterized in that: The steps include: The choline chloride, oxalic acid, magnesium source, iron source and citric acid are mixed and subjected to complexation reaction to obtain a sol; Adjusting the pH of the sol and heating it to obtain a gel; igniting the gel to obtain a precursor after combustion; The precursor is calcined to obtain the magnetic composite adsorbent for removing malachite green dye.
2. The method for preparing a magnetic composite adsorbent for removing malachite green dye according to claim 1, characterized in that: The molar ratio of the magnesium element in the magnesium source to the iron element in the iron source is 1.2-1.6:
2.
3. The method for preparing a magnetic composite adsorbent for removing malachite green dye according to claim 1, characterized in that: The molar ratio of the choline chloride to the oxalic acid is 0.5-1.5:1.5-2.
5.
4. The method for preparing a magnetic composite adsorbent for removing malachite green dye according to claim 1, characterized in that: The ratio of the molar amount of the citric acid to the sum of the molar amounts of the magnesium element in the magnesium source and the iron element in the iron source is 1 to 1.5:
1.
5. The method for preparing a magnetic composite adsorbent for removing malachite green dye according to claim 1, characterized in that: The temperature of the complexation reaction is 40-90°C.
6. The method for preparing the magnetic composite adsorbent for removing malachite green dye according to claim 1, characterized in that: The pH of the sol is adjusted to 7-11; And / or, the calcination temperature is 450-900°C.
7. A magnetic composite adsorbent for removing malachite green dye, characterized in that: The invention is mainly prepared by the preparation method of the magnetic composite adsorbent for removing malachite green dye as claimed in any one of claims 1 to 6.
8. The magnetic composite adsorbent for removing malachite green dye according to claim 7, characterized in that: The main components of the magnetic composite adsorbent for removing malachite green dye include magnesium ferrite, α-ferric oxide and carbon material.
9. Use of the magnetic composite adsorbent for removing malachite green dye according to any one of claims 7 to 8 in removing malachite green dye.
10. Use of the magnetic composite adsorbent for removing malachite green dye according to claim 9 in removing malachite green dye, characterized in that: The magnetic composite adsorbent for removing malachite green dye has a removal rate of ≥90% for a malachite green solution with a concentration of ≤100 mg / L.